Dissolved Thorium Isotope Evidence for Export Productivity in the Subtropical North Pacific During the Late Quaternary. Issue 11 (27th May 2020) - Liu, Ruolin; Wang, Maoyu; Li, Weiqiang; Shi, Xuefa; Chen, Tianyu
Abstract: The vast area of the North Pacific subtropical gyre (NPSG) makes it an important region in exporting biogenic particles and carbon to the deep ocean. Nevertheless, we remain largely ignorant on its past changes in export productivity, leaving an important gap in the understanding of ocean‐climate interactions during the late Quaternary. Here, we take a novel approach to study the particle export via reconstruction of dissolved 230 Th/ 232 Th based on ferromanganese crusts in deep waters of the NPSG at 3.8‐ and 2.8‐km water depth, respectively. The U‐series data indicate stable growth rates of both samples and a rather small variability of their initial ( 230 Th/ 232 Th) in the last ca. 0.7 Myr. These glacial–interglacial integrated values are only about half of the modern dissolved ( 230 Th/ 232 Th) in the deep NPSG, reflecting increased dust dissolution and also particle scavenging related to ~10–40% higher average export productivity than today. Plain Language Summary: Quantitative reconstruction of biogenic particle export to the deep ocean is essential to the understanding of carbon transfer between the ocean and the atmosphere during the past ice age cycles. However, an important knowledge gap still exists on the past biogenic particle export in the deep North Pacific subtropical gyre. Dissolved radionuclides 230 Th and 232 Th in seawater provide a unique tool to study past export particle flux. We have carried out Th isotope analysis of two excellently laminated and densely grown ferromanganese crusts collected from the subtropical North Pacific seamounts. Our data are explained by increased ice age dust dissolution as well as a few tens of percents higher average export productivity than today. Therefore, the North Pacific subtropical gyre would be a stronger sink for carbon during colder ice ages, possibly as a result of increased iron fertilization or other nutrient supply. Key Points: Hydrogenetic ferromanganese crust provides an archive of past seawater dissolved ( 230 Th/ 232 Th) signatures Consistently lower glacial–interglacial integrated ( 230 Th/ 232 Th) than the present is observed in deep waters of the NPSG Glacial–interglacial average export productivity is higher by a few tens of percents than the present in the NPSG